Mosaic‐Structured Cobalt Nickel Thiophosphate Nanosheets Incorporated N‐doped Carbon for Efficient and Stable Electrocatalytic Water Splitting. (6th September 2018) - Liang, Qinghua; Zhong, Lixiang; Du, Chengfeng; Zheng, Yun; Luo, Yubo; Xu, Jianwei; Li, Shuzhou; Yan, Qingyu
Abstract: Engineering the nanostructures and compositions of 2D layered metal thiophosphates (MTPs) is significant for extending their applications. Here, a scalable and flexible strategy is presented to prepare single crystalline CoNiPS3 incorporated with N‐doped carbon (CoNiPS3 /C) nanosheets (≈16 nm thickness), which can be further processed into the mosaic‐structured CoNiPS3 /C nanosheets (≈6 nm thickness) composed of randomly distributed crystalline nanodomains (≈15 nm diameter) and disordered boundaries (denoted as mosaic CoNiPS3 /C nanosheets), and further into separated CoNiPS3 /C nanodots (≈4 nm diameter). The initial CoNiPS3 /C nanosheeets are prepared by using Co–Ni Prussian‐blue analogue nanoplates as templating precursors. As compared to the initial CoNiPS3 /C nanosheets and nanodots, the mosaic CoNiPS3 /C nanosheets exhibit plenty of active edge sites, retained crystallinity, and good structural stability. Synergistically, density functional theory calculations reveal that the bimetallic composition results in higher intrinsic activity, better conductivity, and lower kinetic energy barriers for bifunctional oxygen/hydrogen evolution reactions. More importantly, a water‐splitting electrolyzer constructed using the mosaic CoNiPS3 /C nanosheets as both cathode and anode achieves 30 mA cm −2 at 1.62 V, which is better than the initial CoNiPS3 /C nanosheets (1.69 V) and is comparable to the discreted nanodots (1.58 V). Besides, the mosaic CoNiPS3 /C nanosheets show much better electrocatalytic stability than nanodots. Abstract : Mosaic‐structured CoNiPS3 nanosheets incorporated with N‐doped carbon are developed as electrocatalysts for promoting intrinsic activity, reaction kinetics, and stability of water splitting. An electrolyzer constructed using the CoNiPS3 /C nanosheets as both cathode and anode achieves 30 mA cm −2 at 1.62 V as well as good stability.